Melon and watermelon cultivation technology in Uzbekistan - Chorshanbiyev Panji Khudoymurat oʻgʻli (Zien Journals, 2022)
This article provides information about the policing network, the technology of planting and growing melons and watermelons in Uzbekistan.
Keywords: policing, agriculture, melon, watermelon, variety, land, pumpkin, composition, climate.